👤

Rezolvati ecuatiile :
[tex]1) \\ \frac{ {x}^{2} }{ \sqrt{11} - \sqrt{7} } = \sqrt{11} + \sqrt{7} \\[/tex]
[tex]2) \\ {(x - 6)}^{2} = 24[/tex]
[tex]3) \\ 3 {(x + \frac{1}{3} )}^{2} + \frac{2}{3} = 9[/tex]
Urgent dau 50 de puncte .
[tex] \alpha [/tex]


Răspuns :

Răspuns:

Explicație pas cu pas:

x^2 = (√11 - √7)(√11 + √7) = 11 - 7 = 4

x1 = 2

x2 = -2

________________

(x - 6)^2 = 24

x - 6 = √24 sau -√24

x1 = √24 + 6

x2 = -√24 + 6

________________

3(x + 1/3)^2 = 9 - 2/3 = 27/3 - 2/3 = 25/3

(x + 1/3)^2 = 25/3 : 3 = 25/9

x + 1/3 = 5/3 sau - 5/3

x1 = 5/3 - 1/3 = 4/3

x2 = -5/3 - 1/3 = -6/3 = -2